Neuropathic damage in the diabetic eye: clinical implications. (December 2020) - Simó, Rafael; Frontoni, Simona
Abstract : In recent years, emerging evidence support that the eye is target of diabetes neuropathy. There are two components of the eye that are mainly involved in the neurodegenerative process induced by diabetes: the retina and the cornea. The study of functional and structural changes in these components of the eye will provide useful information to identify subjects with diabetes at risk of diabetic peripheral neuropathy and dementia. In this review the state of the art regarding the evidence and clinical implications of this emerging concept will be provided. In addition, the relationship between retinal and corneal neurodegeneration with peripheral neuropathy and cognitive decline will be analyzed. Finally, the scientific gaps than need to be covered and will be critically examined.